(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of placenta previa and its associated factors among pregnant women delivering at Ca Mau Obstetrics and Pediatrics Hospital during the period 2023–2024. Methods: A cross-sectional descriptive study was conducted on 5,348 pregnant women who delivered at Ca Mau Obstetrics and Pediatrics Hospital. The status of placenta previa and associated factors were analyzed using logistic regression analysis. Results: The prevalence of placenta previa was 3.14%. Among these cases, total placenta previa (placenta previa centralis) accounted for the highest proportion (58,33%), followed by marginal placenta previa (19.64%), partial placenta previa (17,26%), and low-lying placenta (4.77%). Multivariable analysis showed that factors associated with placenta previa included a history of placenta previa (aOR = 6.13; 95% CI: 2.32–9.81; p < 0.001), a history of cesarean section (aOR = 2.38; 95% CI: 1.25–4.47; p < 0.001), multiparity (aOR = 1.43; 95% CI: 1.01–2.03; p = 0.044), maternal age ≥ 35 years (aOR = 1.72; 95% CI: 1.24–2.40; p = 0.001), and a history of induced abortion or curettage (aOR = 1.62; 95% CI: 1.13–2.34; p = 0.009). Conclusions: The prevalence of total placenta previa is relatively high. Obstetric history, specifically a history of placenta previa and prior Cesarean sections, represents significant risk factors, highlighting the necessity for risk screening and intensive monitoring for high-risk pregnant women